ag5Tools: An R package for downloading and extracting agrometeorological data from the AgERA5 database - Brown, David; Sousa, Kauê de; Etten, Jacob van (Elsevier, 2023)
Agrometeorological data is important in agricultural research, especially in agronomy and crop science, for investigating genotype by environment interactions. The AgERA5 dataset from the Copernicus Climate Data Store provides free and public access to global gridded daily agrometeorological data, from 1979 to present, with ready to use variables tailored for agricultural and agro-ecological studies. We developed the R package ag5Tools, which provides a simplified interface for downloading and extracting AgERA5 data. The package facilitates extracting time-series data for sets of geographic points in a format that can be conveniently used in statistical models applied in agricultural research. The use of the package is demonstrated with a synthetic dataset of multi-location trials in Arusha, Tanzania.